Outcomes of elective endovascular aneurysm repair in patients receiving chronic kidney replacement therapy from a binational data linkage study - Hinde, Darcy; Palamuthusingam, Dharmenaan; Hawley, Carmel M.; Pascoe, Elaine M.; Johnson, David Wayne; Pinto, Nigel; Fahim, Magid (Journal of vascular surgery, 2025)
Our study aims to define the rates of mortality and nonfatal complications in patients with kidney failure undergoing elective endovascular aortic aneurysm repair (EVAR) for the management of infrarenal abdominal aortic aneurysm (AAA) in Australia and New Zealand. A retrospective binational data linkage between the Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) and state-based health-related datasets identified patients receiving chronic kidney replacement therapy (KRT) who underwent EVAR for AAA between January 1, 2000, and December 31, 2015. Linked data were interrogated to define patient demography, modality of KRT, date of death, and the occurrence of specific nonfatal complications. Patients were categorized by modality (hemodialysis [HD], peritoneal dialysis [PD], home hemodialysis [HHD], and kidney transplant [KT]), and logistic regression analysis was used to determine the rates of 30-day and 12-month mortality, as well as nonfatal postoperative complications. During the study period, 367 patients receiving KRT underwent 397 EVAR procedures for AAAs. Of these, 216 (54%) were performed electively, and 181 (46%) were performed emergently. The rate of elective EVAR was 0.25 per 100 patient-years, with the majority of cases (51%) occurring in patients receiving HD. Overall, 30-day mortality following elective EVAR was 2.7% (95% confidence interval [CI], 0.4-5.1), with HD patients being at greatest risk at 4.2% (95% CI 0.4-8.0). Postoperative infective complications were more common than cardiovascular complications. Twelve-month mortality following elective EVAR was 18.3% (95% CI, 13.1%-23.4%) for the entire cohort, with HD and PD patients being at approximately equivalent risk. All adverse outcomes were observed with greater frequency following emergency EVAR compared with those undertaken electively. Patients on chronic KRT have high rates of morbidity and mortality following elective EVAR. This should be accounted for during shared decision-making and when considering the relationship between risk and benefit in the management of AAAs in this population.